Latent common genetic components of obesity traits - Tayo, BO (2008)
BACKGROUND: Obesity is rapidly becoming a global epidemic. Unlike many complex human diseases, obesity is defined not just by a single trait or phenotype, but jointly by measures of anthropometry and metabolic status. METHODS: We applied maximum likelihood factor analysis to identify common latent factors underlying observed covariance in multiple obesity-related measures. Both the genetic components and the mode of inheritance of the common factors were evaluated. A total of 1775 participants from 590 families for whom measures on obesity-related traits were available were included in this study. RESULTS: The average age of participants was 37 years, 39% of the participants were obese (body mass index ≥ 30.0 kg/m(2)) and 26% were overweight (body mass index 25.0 - 29.9 kg/m(2)). Two latent common factors jointly accounting for over 99% of the correlations among obesity-related traits were identified. Complex segregation analysis of the age and sex-adjusted latent factors provide evidence for a Mendelian mode of inheritance of major genetic effect with heritability estimates of 40.4% and 47.5% for the first and second factors, respectively. CONCLUSIONS: These findings provide a support for multivariate-based approach for investigating pleiotropic effects on obesity-related traits which can be applied in both genetic linkage and association mapping.